Analisis I Ketersediaani Fasilitasi Petugasi Aproni Movementi Controli Dalam Mendukung Operasional Di Bandar Udarai Abdulrachman Saleh Malang - Helmi Yudiyansyah; Zenita Kurniasari (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2023)
Apron Movement Control (AMC) officers when operating must maximize existing facilities so that there are additional facilities that are lacking in the AMC unit. This study aims to find out what types of work facilities must be available to assist the operation of iApron Movement Control officers at Abdulrachmani Salehi Malang Airport and to determine the availability of the number of facilities that must be available to assist the operation of Aproni Movement Control officers at Abdulrachmani Saleh Airport Malang. This study uses a qualitative and quantitative approach with data collection techniques using qualitative observation, structured interviews, and documentation while quantitative uses the AMC unit facility data form, and observations, which were collected from relevant informants when the writer went to the field. The results of this study indicate that the types of facilities that must be available in the operation of Apron Movement Control officers are Personal Protective Equipment (PPE), personal protective equipment in the form of safety vests, raincoats, hats, safety shoes, booth shoes, ear muffs & ear plugs, goggles anti uv where these facilities must be available in the AMC unit. These facilities are very important to assist officers. Facilities that are not available, such as safety shoes, booth shoes, ear muffs & ear plugs, anti-UV goggles that are not available and an insufficient number of ear muffs and ear plugs, this was responded to by the Chairman of AMC.